Pengembangan Virtual Tour 360 Derajat Sebagai Media Informasi Wisata Curug Sanghyang Taraje Berbasis Web - Algifari, M.; Deddy Supriatna, Asep (Institut Teknologi Garut, 2025)
Curug Sanghyang Taraje is a natural tourist attraction in Garut Regency that holds significant aesthetic potential but remains relatively unknown due to limited access to engaging promotional media. This study aims to develop an information platform based on interactive 360-degree virtual tour technology, accessible via a website, to provide users with an engaging and informative visual exploration experience. The application development follows the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collection, production, testing, and distribution. The 3DVista software is used to construct the virtual tour, while integration into the website is carried out using Visual Studio Code with HTML, CSS, and JavaScript. Key features of the application include 360-degree panoramic views, informational text, narrated audio, interactive navigation via hotspots, background music, and a digital map. Testing is conducted using a black-box approach with decision table techniques to ensure all functions meet user requirements. The result of this research is an interactive virtual tour application that comprehensively presents tourism information and serves as a digital promotional tool for tourism managers. The application facilitates tourists in exploring the destination remotely and demonstrates that virtual tour technology can be an innovative solution to support digital tourism promotion.